INSURANCE MARKET AND SYSTEM-BASED RISK OF FUNCTIONING - O. I. Shevtsova; Yе. I. Bondar (Фінансово-кредитна діяльність: проблеми теорії та практики)
The article deals with the factors and conditions for the emergence and spread of systemic risks in the insurance market within the framework of the interaction of insurance companies with each other and other financial institutions. These are forms of identifying the features of systemic risk manifestation. Focused attention is paid to factors such as competition between financial institutions, mergers and acquisitions, accumulation of individual risks, and their impact on the characteristics of the insurance market, markets of other financial intermediaries. The conditions of distribution of systemic risks — the increase of the level of capitalization of the insurance market, a separate insurance company, the presence of the transfer of risks from one to another financial intermediary.